The Role of Quilting Technique of Mastectomy Flap in Prevention and Reduction of Seroma Complication in Breast Cancer Patients - Mohend Abbass (Journal of Global Pharma Technology, 2018)
Background: Seroma remains an unresolved problem Post mastectomy surgery and several techniques have been reported to prevent or decrease this complication. The aim of this study is to evaluate effectiveness of Quilting or tacking mastectomy flap in preventing or reducing seroma formation. Patients and Method: This hospital-based prospective cohort study included patients with diagnosed breast cancer between December 2010 and December 2016. Mastectomy with axillary clearance surgery was done for them. Socio-demographic Characteristics which include age, BMI, smoking history and family history of breast cancer were taken for all patients. Data were collected on the day of surgery and followed for two weeks postoperatively. Patients were divided in two groups according to the technique of closure of mastectomy flap . Non quilting technique was done to the first group of patients between December 2010 till January 2014 and the quilting techniques were done for second group of patients between February 2014 till December 2016. Primary outcome were the presence of Seroma complication and the amount of fluid collection that require aspiration. Secondary outcome were the mean differences of fluid drained by the drainage system, time to remove drain, stage of disease, level of axillary clearance, distribution of patients according to type of malignancy, Oestrogen receptor, progesterone receptor and Her2 /Neu receptor status. Result: During the study period between December 2010 and December 2016, 82 Patients with diagnosed breast cancer were included in this study. Majority (84.1%) of patients presented with Invasive ductal carcinoma. There was significant association between type of operation and presence of seroma, more seroma occur among patients treated with Non quilting technique (46.8%) in comparison to quilting technique (20%) (P- value 0.012) and more time needed to remove drain among patients treated with Non quilting technique (with mean 5.74 days) in comparison to quilting technique (with mean 4.74 days). There were significant differences between means of amount of aspiration among patients with seroma (n=29) by study groups, more amount of aspiration among patients treated with Non quilting technique (with mean 144.54 ml) in comparison to quilting technique (with mean 60.71 ml). There was significant association between presence of seroma and BMI (P- value <0.001) and level of clearance (P-value 0.021) and no association between presence of seroma and Smoking, family history and stage of disease. Conclusion: Quilting or tacking mastectomy flap to the underlying muscles and fascia to obliterate the surgical dead space is effectiveness in prevention and reduction of seroma formation.Keywords: Breast cancer, Mastectomy flap, Quilting technique.